A novel cell-based assay for the high-throughput screening of epithelial–mesenchymal transition inhibitors: Identification of approved and investigational drugs that inhibit epithelial–mesenchymal transition. (January 2023) - Ishikawa, Hiroyuki; Menju, Toshi; Toyazaki, Toshiya; Miyamoto, Hideaki; Chiba, Naohisa; Noguchi, Misa; Tamari, Shigeyuki; Miyata, Ryo; Yutaka, Yojiro; Tanaka, Satona; Yamada, Yoshito; Nakajima, Daisuke; et al.
Highlights: ・Evaluating EMT inhibitors for non-small cell lung cancer in a screening. ・Selected compounds were confirmed by Western blotting and invasion assays. ・Four compounds were identified, and two compounds inhibited cell invasiveness. Abstract: Objectives: Lung cancer with distant metastases is associated with a very poor prognosis, and epithelial-mesenchymal transition (EMT) contributes to cancer metastasis. Therefore, elucidation and inhibition of EMT signaling in lung cancer may be a new therapeutic strategy for improving the prognosis of patients. We constructed a high-throughput screening system for EMT inhibitors. Using this system, we aimed to identify compounds that indeed inhibit EMT. Materials and methods: We generated a luciferase reporter cell line using A549 human lung cancer cells and E-cadherin or vimentin as EMT markers. EMT was induced by transforming growth factor β1 (TGF-β1), and candidate EMT inhibitors were screened from a library of 2, 350 compounds. The selected compounds were further tested using secondary assays to verify the inhibition of EMT and invasive capacity of cells. Results: Values obtained by the assay were adjusted for the number of viable cells and scored by determining the difference between mean values of the positive and negative control groups. Four compounds were identified as novel candidate drugs. Among those, one (avagacestat) and two compounds (GDC-0879 and levothyroxine) improved the expression of E-cadherin and vimentin, respectively, in epithelial cells. GDC-0879 and levothyroxine also significantly inhibited the invasive capacity of cells. Conclusion: We systematically screened approved, investigational, and druggable compounds with inhibitory effects using a reporter assay, and identified candidate drugs for EMT inhibition.